Expression profiles of α-synuclein in cortical lesions of patients with FCD IIb and TSC, and FCD rats - Zhang, Li; Huang, Jun; Dai, Lu; Zhu, Gang; Yang, Xiao-Lin; He, Zeng; Li, Yu-Hong; Yang, Hui; Zhang, Chun-Qing; Shen, Kai-Feng; Liang, Ping (Frontiers in Neurology, 2023)
Background Focal cortical dysplasia (FCD) IIb and tuberous sclerosis complex (TSC) are common causes of drug-resistant epilepsy in children. However, the etiologies related to the development of FCD IIb and TSC are not fully understood. α-synuclein (α-syn) is a member of synucleins family that plays crucial roles in modulating synaptic transmission in central nervous system. Here, we explored the expression profiles and potential pathogenic functions of α-syn in cortical lesions of epileptic patients with FCD IIb and TSC. Methods Surgical specimens from epileptic patients with FCD IIb and TSC, as well as FCD rats generated by in utero X-ray-radiation were adopted in this study and studied with immunohistochemistry, immunofluorescence, western blotting, and co-immunoprecipitation etc. molecular biological techniques. Result Our results showed that α-syn expression was reduced in FCD IIb and TSC lesions. Specifically, α-syn protein was intensely expressed in dysplastic neurons (DNs) and balloon cells (BCs) in FCD IIb lesions, whereas was barely detected in DNs and giant cells (GCs) of TSC lesions. Additionally, p-α-syn, the aggregated form of α-syn, was detected in DNs, BCs, GCs, and glia-like cells of FCD IIb and TSC lesions. We previous showed that the function of N-methyl-D-aspartate receptor (NMDAR) was enhanced in FCD rats generated by X-ray-radiation. Here, we found the interaction between α-syn and NMDAR subunits NMDAR2A, NMDAR2B were augmented in cortical lesions of FCD patients and FCD rats. Conclusion These results suggested a potential role of α-syn in the pathogenesis of FCD IIb and TSC by interfering with NMDAR.